2021
DOI: 10.14687/jhs.v18i4.6257
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder and physical activity

Abstract: Aim: The aim of the study is to examine the relationship between autism spectrum disorder and physical activity in depth. Findings: Autism was first defined by Bleuler, but the history of autism as a term began with the founding of the first pediatric psychiatry clinic by Kanner. Later, autism was defined and revised in the Diagnostic and Statistical Manual of Mental Disorders of the American Psychiatric Association (APA) in various periods before currently being expressed by criteria, ratings, and classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is reported that this situation leads to an increase in the self-efficacy beliefs of the participants, thus enabling an increase in the quality of life of individuals with physical disabilities. In this context, it can be said that the positive social support that individuals with disabilities receive directly or indirectly is important in their motivation to participate in a physical activity ( Durmuş et al, 2021 ; Olsen et al, 2023 ). Within the scope of the research findings, it can be stated that increasing encouraging factors for the participation of disabled athletes in sports and promoting their participation could enhance their respective motivations.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that this situation leads to an increase in the self-efficacy beliefs of the participants, thus enabling an increase in the quality of life of individuals with physical disabilities. In this context, it can be said that the positive social support that individuals with disabilities receive directly or indirectly is important in their motivation to participate in a physical activity ( Durmuş et al, 2021 ; Olsen et al, 2023 ). Within the scope of the research findings, it can be stated that increasing encouraging factors for the participation of disabled athletes in sports and promoting their participation could enhance their respective motivations.…”
Section: Discussionmentioning
confidence: 99%